2013
DOI: 10.1007/s00167-013-2404-4
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic and histologic analysis of the mid-substance and fan-like extension fibres of the anterior cruciate ligament during knee motion, with special reference to the femoral attachment

Abstract: The present study clarified anatomic and histologic character of the mid-substance fibres and fan-like extension fibres, and provided critical information for future clinical and biomechanical studies concerning both two different fibres. Specifically for ACL reconstruction, it is difficult to reconstruct the natural fan-like extension fibres by creating a tunnel at the femoral and tibial ends of each fibre bundle, although the mid-substance fibres can be reconstructed by such procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
106
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(114 citation statements)
references
References 24 publications
2
106
2
2
Order By: Relevance
“…Shino et al reported similar findings with the more detailed histological study [26,27]. However, a recently new concept of the anatomy of the femoral insertion was published by several authors [28,29]. They found by anatomical dissection that the predominantly functioning femoral insertion of ACL existed more anteriorly than was reported [28].…”
Section: Insertion Site Evaluationmentioning
confidence: 58%
“…Shino et al reported similar findings with the more detailed histological study [26,27]. However, a recently new concept of the anatomy of the femoral insertion was published by several authors [28,29]. They found by anatomical dissection that the predominantly functioning femoral insertion of ACL existed more anteriorly than was reported [28].…”
Section: Insertion Site Evaluationmentioning
confidence: 58%
“…Although there is no definite reason for the result, previous anatomical studies indicated that the femoral attachment of the ACL can be separated into two different fiber types, the direct insertion and indirect insertion (Mochizuki et al, 2014;Sasaki et al, 2012;Smigielski et al, 2015). The ACL fibers connected to the direct insertion are flexible and can respond to forces from any direction, while the ACL fibers connected to the indirect insertion are simple fibers and work like anchors (Mochizuki et al, 2014;Sasaki et al, 2012). Since the ACL fibers in the lateral layer mainly consist of the former fibers in the femoral attachment, the strain behavior in response to an anterior load may be different as compared with those in the medial and middle fibers.…”
Section: Discussionmentioning
confidence: 99%
“…Some macroscopic and histologic anatomic studies suggest variability of the normal ACL femoral attachment. Mochizuki et al [12] demonstrated the differences of the indirect insertion area among the subjects, because the variety of the lateral wall shape of the intercondylar notch is not small, but rather quite large. Meanwhile, the direct insertion is narrow and exists constantly at the dome of the intercondylar space and at the posterior cortex of the femoral condyle.…”
Section: Discussionmentioning
confidence: 99%